Marine fouling: Factors affecting biofouling and future perspectives - Nikolaos D Papadopoulos; Polyxeni Vourna; Sotirios Xafakis; Nikos Stefanakis; Paraskevi Vourna (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2023)
Biofouling of the hulls of ships and vessels, caused by the colonization of animals and plants, is an ongoing problem for the shipping industry. Biofouling evokes surface roughness, which results in higher fuel consumption, emissions, and operating costs. Mitigation of biofouling is a complex problem and the effectiveness of any given approach depends on many factors. Compared to complex anti-fouling technologies, the use of anti-fouling coatings presents the most viable solution, both in terms of cost and efficiency. Nevertheless, due to the modest performance of most modern antifouling hull coatings, frequent maintenance, and dry-docking intervals are still required. In addition, application costs are often not negligible. New antifouling technologies, such as low-drag antifouling paints with broad spectrum activity are urgently required in order to promote smoothness of the surface as well as provide adequate protection against biofilm formation. The development of innovative nanocomposite coating structures which combine low-drag film surfaces with antimicrobial components within water-soluble matrices may be a drastic solution to the above problem. Moreover, applying such structures directly on the hulls of ships and marine vessels without the use of primers is a long-awaited possibility, which could have a tremendous impact on reducing application costs.